Check List of Angiosperms in 30 km Radius of Kudankulam Nuclear Power Project - Sekar, Ramarajan; Murugesan, A. G. (Indian Forester, 2019)
A total of 665 plant species belonging to 419 genera and 108 families were recorded from the entire 30 km radius of KKNPP (except reserve forest Mahendragiri hill) of flowering plants. A checklist of these species is provided here.